Control of liver abscesses in lambs by using marbofloxacin - ORFANOU (Δ.Κ. ΟΡΦΑΝΟΥ) D. C.; FRAGKOU (Η.Α. ΦΡΑΓΚΟΥ) Ι. Α.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ) G. C.; MAVROGIANNI (Β.Σ. ΜΑΥΡΟΓΙΑΝΝΗ) V. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
We describe cases of liver abscesses in a group of newborn lambs. Diagnosis was based on the combination of clinical signs with the findings of ultrasonographic examination of the abdomen: oval, hypoechoic structure with regular borders in the liver of the affected lambs. Administration of marbofloxacin (dose rate: 3.0 mg per kg body weight, on three occasions, once daily, two days apart) was effective for treatment; three weeks later, the affected lambs were clinically health.